Pengaruh Ekstrak Undur-undur (Myrmeleon sp) terhadap Glukosa Darah dan Hematokrit pada Tikus Diabetes - Djap Hadi susanto; Ronald Winardi Kartika; Pamela Hendra Heng; Adit Widodo Santoso; Maria VB Lopulalan; Angelina Wijaya (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2020)
Diabetes Mellitus (DM) is one of the major health problems in the world and Indonesia. The prevalence is more increasing and also shows the trend of events is shifting to young age. Diabetes mellitus treatment requires high costs and also a lifetime. Most of the people of Indonesia still use traditional methods of treatment, especially herbs from various biological substances that are available in the environment. Undur-undur (myrmeleon sp.) is believed to have the effect of anti-hyperglycemia, and also anti-viscosity. The aim of this study was to determine anti-hyperglycemia and anti-viscosity of myrmeleon sp. extract in diabetic rats. The design of study is randomized experiment. Diabetic rats were induced by streptozocin 100mg/ kg BW intraperitoneal. Fifty rats were divided into 2 groups administered by Myrmeleon sp. extract dose 0,01ml/ 200 gram BW (100%) and 0,005ml/ 200 gram BW (50%). Myrmeleon sp. shows the effect of anti-hyperglycemic and anti-viscosity in diabetic rats. There was a difference between 50% and 100% doses. The effect of anti-hyperglycemia and anti-viscosity occurs after the second day. Conclusion: the extract of myrmeleon sp. could be considered as one of the traditional treatments of diabetic patients.